Penerapan Active Learning Pada Pembelajaran Ipa - Mardiyah, Intihatun (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
The result of the research shown that teacher of science in the fifth grade has beenimplemented active learning strategy which is including eight indicators and according toMelvin L. Silberman’s theory, they are full-class learning, calss discussion, questionprompting, collaborative learning, peer teaching, independent learning, affective learning,and skill development. In the learning process, teacher is implementing eight indicators ofactive learning in the science learning. Each MI has been done well implementing activelearning indicators, but there are still any indicators which haven’t done maximally. Theresearcher is comparing the implementation of active learning in the science learning inthree Islamic elementary schools (MI). From each aspects of active learning have its ownexcess, weakness, development chance and obstacle in the implementation of sciencelearning.